Perlindungan Atas Hak Kehidupan (Right To Life) Masyarakat Rempang - Sodikin, Sodikin (Journal of Contemporary Law Studies, 2025)
The right to life includes the entitlement of every individual to a good and healthy environment. It is essential for the state to protect these human rights, including the right to life of the Rempang community. The focus of this writing is to investigate how the right to life of the Rempang residents is safeguarded under existing laws and regulations. The research employs a normative juridical method, aiming to identify and formulate legal arguments through problem analysis. The findings indicate that, constitutionally, the Rempang community's rights are guaranteed by Article 28H, paragraph (1) of the 1945 Constitution. These rights are further implemented through various laws, including Law Number 32 of 2009 concerning Environmental Protection and Management, Law Number 39 of 1999 concerning Human Rights, and Law Number 17 of 2023 concerning Health. In addition to these national laws, several international conventions also address the right to a healthy environment, which serves as a foundation for states to develop policies that protect human rights within the community. There is also a pressing need for reaffirming law enforcement in regards to human rights, particularly the right to a good and healthy environment, as mandated by existing laws and regulations. The government is expected to act in order to protect, fulfill, and respect human rights, especially the right to a good and healthy environment, at all levels of society